A Comparative Analysis Of Capital Expenditure On Infrastructure And Economic Growth In Nigeria And South Africa - Ayeni, R. K.; Olasehinde, Ireti Olamide (Archives of Business Research, 2020)
Nigeria and South Africa are two dominating economies in Africa but defer in terms of infrastructural development. The question of whether this infrastructural difference culminate to the difference in economic growth in the two economies is central to this study. This paper therefore, examined the impact of capital expenditure on infrastructure and economic growth both in Nigeria and South Africa using time series data from 1980 to 2016. Autoregressive Distributed Lag (ARDL) Bound tests technique of cointegration was used to on country-specific model of aggregate expenditure, following the Keynesian theory. The result showed that there is a the long-run relationship among the variables used in Nigeria and South Africa. Capital expenditure on infrastructure has positive but insignificant impact on economic growth in Nigeria while it was positive and significant on the economic growth in South Africa. The insignificant impact of capital expenditure on infrastructure on economic growth compare with South Africa may be the major difference in the two economies. This is traceable to lack of accountability and corruption in Nigeria compared to the good governance that truncated corruption and mismanagement in the government circle in South Africa. Tax base has positive and significant impacts on the economic growth in these two countries, this was supported by the Pairwise Granger Causality in which TAX granger caused economic growth in both countries. The study recommends injection of sufficient fund into infrastructural development in Nigeria. AS tax contributed positively to economic growth in both economies, it is recommended that tax revenue realized should be judiciously spent by providing the necessary amenities to discourage evasion of tax.